Semitic languages Its characteristics and importance in the interpretation of some linguistic phenomena (Journal of the College of Basic Education, 2022)
The research dealt with the Semitic languages, talked about the concept of the term, the opinion of some Arab linguists about it, and the need to replace this term with a term consistent with scientific, historical and geographical facts. The research focused on the geographical distribution of these languages, reviewing their linguistic characteristics. Phonetic, morphological, grammatical, and semantic. He also pointed out the differences between northern and southern languages. The research studied linguistic phenomena in the Yemeni dialect and in classical Arabic, and the persistence of some phenomena that are difficult to change despite the many nights and days, which is due to the mother Semitic, or to one of the languages ​​branching from it. Referring to some of the linguistic development in eloquent use in various phenomena, which the opinions of Arab linguists in the past differed about, and the modernists interpreted it in the light of the Semitic languages.